5 - Academic Freedom in Africa: Revisiting the Kampala Declaration - Journal System, (CODESRIA Bulletin, 2025)
CONFERENCE CALL FOR PAPERS Venue: University of Dar es Salaam, Dar es Salam, Tanzania Date: 29 April – 2 May 2025 Concept Note In November 1990, CODESRIA organised a landmark conference in Kampala, Uganda, where the Kampala Declaration on Intellectual Freedom and Social Responsibility was adopted. Coming just a few months after the Dar es Salaam Declaration on Academic Freedom and Social Responsibility of Academics, the Kampala Declaration provides a broad pan-African framework for the protection of intellectual and academic freedom on the continent. The Dar es Salaam and Kampala declarations were historic responses to new trends in society in general but speciﬁcally in the higher education sector.